2004
DOI: 10.1016/j.febslet.2004.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Cohesin–dockerin interaction in cellulosome assembly: a single Asp‐to‐Asn mutation disrupts high‐affinity cohesin–dockerin binding

Abstract: The cohesive cellulosome complex is sustained by the high-affinity cohesin-dockerin interaction. In previous work [J. Biol. Chem. 276 (2001) 9883], we demonstrated that a single Thr-to-Leu replacement in the Clostridium thermocellum dockerin component differentiates between non-recognition and highaffinity recognition by the interspecies rival cohesin from C. cellulolyticum. In this report, we show that a single Asp-toAsn substitution on the cohesin counterpart also disrupts normal recognition of the dockerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 33 publications
5
51
0
Order By: Relevance
“…The equivalent residues in the WT dockerin; Asn-44B, Thr-49B, Ser-52B and Arg-23B (N 2), respectively, do not make direct interactions with the cohesin (SI Table 5). Mutagenesis studies support the importance of the polar interactions between the cohesin residues Ala-36A, Asn-37A, Asp-39A, Tyr-74A, Glu-86A, Gly-89A and Glu-131A (26,27) and type I dockerins, although the functional significance of Arg-77A, which seems to make important hydrogen bonds with Arg-23B and Arg-57B at the C-terminal end of the two dockerin binding sites, has not previously been explored.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The equivalent residues in the WT dockerin; Asn-44B, Thr-49B, Ser-52B and Arg-23B (N 2), respectively, do not make direct interactions with the cohesin (SI Table 5). Mutagenesis studies support the importance of the polar interactions between the cohesin residues Ala-36A, Asn-37A, Asp-39A, Tyr-74A, Glu-86A, Gly-89A and Glu-131A (26,27) and type I dockerins, although the functional significance of Arg-77A, which seems to make important hydrogen bonds with Arg-23B and Arg-57B at the C-terminal end of the two dockerin binding sites, has not previously been explored.…”
Section: Resultsmentioning
confidence: 98%
“…3). Whereas the role of indirect hydrogen bonds in protein ligand recognition is controversial (28,29), mutating the cohesin residue Asp-39A, which makes solvent-mediated hydrogen bonds with the backbone carbonyl and amines of the dockerin residues Ile-43B, Ile-19B, Val-21B and Leu-55B, reduces affinity 1000-fold (26), suggesting that these interactions may be important in cohesin-dockerin binding. Furthermore, the cohesin residue Thr66A, which makes a solvent-mediated hydrogen bond with Lys18B, when the C-terminal binding site of the dockerin interacts with its protein ligand, is not invariant in the CipA cohesins.…”
Section: Resultsmentioning
confidence: 99%
“…Although the sequences of C. cellulolyticum type I cohesins and dockerins are very similar to the corresponding C. thermocellum modules, there is no cross-specificity between the proteins derived from the two organisms (8,13,16). Significantly the Ser-Thr dyad in the C. thermocellum dockerins is replaced with hydrophobic residues in the corresponding C. cellulolyticum protein modules.…”
mentioning
confidence: 93%
“…As with past work on C. thermocellum, we postulated that the failure to crystallize the complex likely reflected the dynamic interaction of the two potential ligand-binding sites in the dockerin with the cohesin. It has been suggested that the C. cellulolyticum dockerin has two ligand-binding sites in which residues dAla-16 and dLeu-17 at site 1 and dAla-47 and dPhe-48 in site 2 (C. cellulolyticum dockerin residues henceforth are prefaced with d and cohesin residues with c) play a key role in cohesin recognition (8,13,16). To encourage a single binding mode between the protein partners for the equivalent C. cellulolyticum complexes, two variants of the dockerin were constructed in which the functions of site 1 and site 2 were disrupted through the introduction of the mutations A16S/L17T and A47S/F48T, respectively.…”
Section: Thermodynamics and Stoichiometry Of Cohesin-dockerinmentioning
confidence: 99%
See 1 more Smart Citation